Pertanggungjawaban Pidana Pelaku Perundungan (Bullying) Verbal Menyebabkan Bunuh Diri Perspektif KUHP Nasional - adriannisa rakhadennis; Toni, S.H.,M.H; Dr. Rio Armanda Agustian, S.H.,M.H (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study discusses criminal liability for perpetrators of verbal bullying that causes the victim to commit suicide, from the perspective of the Indonesian National Criminal Code (KUHP). Verbal bullying, which includes insults, intimidation, and verbal harassment, can cause severe psychological stress to the point of pushing the victim to end his or her life. Through a normative legal approach, this study analyzes the legal gaps in the National Criminal Code and other related regulations that do not specifically regulate the crime of verbal bullying. Although there are several articles such as Article 462 of the National Criminal Code, Article 27 paragraph (3) of the ITE Law, and Article 335 of the Criminal Code, their implementation still faces difficulties in proving the elements of causality and culpability between the perpetrator's actions and the victim's death. Therefore, a reformulation of the national criminal law is needed that explicitly regulates verbal bullying as a special crime, clarifies its elements, and ensures fair criminal liability for the perpetrator. Keywords: Victims, Criminal Act Perpetrators, Criminal Responsibility, Verbal Bullying